Pemanfaatan Modal Sosial Dalam Pengembangan Sektor Perdagangan Pada Usaha Mikro Kecil dan Menengah (Studi di Tapanuli Utara) - Harisan Boni Firmando (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2021)
Writing a journal entitled "Utilization of Social Capital in the Development of the Trade Sector in Micro, Small and Medium Enterprises (Study in North Tapanuli)" begins with a new economic paradigm that sees multidimensional development reflected in various social perspectives. The trade sector is a solution for the implementation of development, especially from the joints of the national economy. The presence of micro, small and medium enterprises in the trade sector can maintain economic stability, especially in strengthening the structure of the national economy. The method used in this research is descriptive method with a qualitative approach. Data were collected by observation and interviews. The unit of analysis and informants in this study were traders and customers of micro, small and medium enterprises in North Tapanuli. The data were interpreted using field notes. The results show that the use of social capital in micro, small and medium enterprises makes them strong, independent and has high competitiveness, where all business actors play a major role in economic activities, from process, production, distribution to consumption.